The marantaceae of the National Botanic Garden - Macabenta, Jose Paulino C; Capina, Ronito O. (1984)
This study contains a description of the Marantaceae (arrowroot) Family, its genera, and species propagated in the National Botanic Garden (NBG) in Real, Quezon, Philippine Dichotomous keys are provided for easy reference and identification workers were presented
Includes bibliographical references (pages 56)
Keywords: Marantaceae; National botanic garden